Japage: the collapse dolines on Kupres polje, Bosnia and Herzegovina - Stepišnik, Uroš (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2014)
Kupres polje is situated within the Dinaric karst of western Bosnia and Herzegovina. In close proximity to the north-eastern edge of the polje is a group of collapse dolines which are locally referred to as Japage. The study revealed that the position of collapse dolines has been strongly influenced by the lithology governing the formation of a cave system which is undermining material in the subsurface below the dolines. The presence of the undermining process, as well as surface alluvial accumulation, strongly influenced the morphology of the doline floors.
Keywords: Bosna in Hercegovina; Bosnia and Herzegovina; geomorfologija; geomorphology; karst; kras (geologija); krasoslovje; kraški pojavi; Kupreško polje; relief; topography; udornice